Ocean convection linked to the recent ice edge retreat along east Greenland - Kjetil Våge (Nature Portfolio, 2018)
Warm Atlantic water circulates cyclonically around the Nordic Seas while gradually cooling. Here, the authors show that the retreat of the ice edge toward Greenland has led to further transformation of this water mass, which is no longer situated underneath sea ice when transiting the western Iceland Sea in winter.